Electrochemical skin conductance: a tool for risk stratification and early anticipation of diabetic foot ulcers - Gautier, Jean-François; Riveline, Jean-Pierre; Potier, Louis; Bourron, Olivier; Bordier, Lyse; Vittrant, Benjamin; Roussel, Ronan; Bauduceau, Bernard (Frontiers in Endocrinology, 2025)
IntroductionDiabetic foot ulcers (DFUs) are a major complication of diabetes, leading to high morbidity, mortality, and healthcare costs. Current DFU risk stratification relies on clinical examination, which can be subjective. Electrochemical Skin Conductance (ESC), measured via Sudoscan, offers an objective assessment of small fiber dysfunction. This study evaluates the association between ESC and DFU risk stratification.MethodsA retrospective analysis of 2,157 diabetic patients from four tertiary centers in France was conducted. DFU risk was classified using the 2016 International Working Group on Diabetic Foot (IWGDF) grading system. ESC measurements were analyzed alongside age, sex, diabetes type, and monofilament test results. Regression and ROC analyses assessed predictive performance.ResultsESC values correlated with DFU grades (p<0.001), with lower foot ESC (FESC) in higher-risk patients. ROC analysis showed strong predictive value for severe DFUs (AUC = 0.82 for grade 3) but limited performance for early stages. Notably, ESC identified at-risk patients within grade 0, undetected by standard classification.DiscussionESC provides a reproducible, operator-independent tool for DFU risk assessment, improving early detection beyond monofilament testing. These findings support its potential role in DFU prevention, reducing amputations and enhancing patient outcomes. Further studies are needed to validate its prognostic value and integration into clinical care.